Echocardiographic quantification of left ventricular asynchrony predicts an acute hemodynamic benefit of cardiac resynchronization therapy - Breithardt, Ole A.; Stellbrink, Christoph; Kramer, Andrew P.; Sinha, Anil M.; Franke, Andreas; Salo, Rodney; Schiffgens, Bernhard; Huvelle, Etienne; Auricchio, Angelo (Journal of the American College of Cardiology, 2002)
We sought to determine whether radial left ventricular (LV) asynchrony in patients with heart failure predicts systolic function improvement with cardiac resynchronization therapy (CRT). We quantified LV wall motion by echocardiography to correlate the effects of CRT on LV systolic function with wall motion synchrony. Thirty-four patients underwent echocardiographic phase analysis of LV septal and lateral wall motion and hemodynamic testing before CRT. Phase relationships were measured by the difference between the lateral (ΦL) and septal (ΦS) wall motion phase angles: ΦLS = ΦL − ΦS. The absolute value of ΦLS was used as an order-independent measure of synchrony: |ΦLS| = |ΦL − ΦS|. Three phase relationships were identified (mean ± SD): type 1 (n = 4; peak positive LV pressure [dP/dtmax] 692 ± 310 mm Hg/s; ΦLS = 5 ± 6°, synchronous wall motion); type 2 (n = 17; dP/dtmax 532 ± 148 mm Hg/s; ΦLS = 77 ± 33°, delayed lateral wall motion); and type 3 (n = 13; dP/dtmax 558 ± 154 mm Hg/s; ΦLS = −115 ± 33°, delayed septal wall motion, triphasic). A large |ΦLS| predicted a larger increase in dP/dtmax with CRT (r = 0.74, p < 0.001). Sixteen patients were studied during right ventricular (RV), LV and biventricular (BV) pacing. Cardiac resynchronization therapy acutely reduced |ΦLS| from 104 ± 41° (OFF) to 86 ± 45° (RV; p = 0.14 vs. OFF), 71 ± 50° (LV; p = 0.001 vs. OFF) and 66 ± 42° (BV; p = 0.001 vs. OFF). A reduction in |ΦLS| predicted an improvement in dP/dtmax in type 2 patients for LV (r = 0.87, p = 0.005) and BV CRT (r = 0.73, p = 0.04). Echocardiographic quantification of LV asynchrony identifies patients likely to have improved systolic function with CRT. Improved synchrony is directly related to improved hemodynamic systolic function in type 2 patients.